Some Aspects of Harmonisation of Ukraine’s Competition Legislation to EU Standards - Bakalinska, Olga O.; Polyukhovych, Valeriy I.; Korol, Volodymyr I.; Kiriiak, Oksana V. (International Journal of Criminology and Sociology, 2021)
In modern conditions, obtaining information about market dynamics, trends in demand, and alternative offers from competitors is vital to support the effective operation of enterprises. It is also common business practice to discuss legislative initiatives, non-confidential technical information, quality and safety standards, and various aspects of the industry. However, the direct or indirect exchange of information may be accompanied by various wrongful intentions of economic entities (for example, elimination of competitors, creation of entry barriers, agreement on price levels, certain discounts, sales volumes, and the market’s geographical distribution, etc.). In Ukraine, there are currently no analogues of a full-fledged guide to information exchange between competitors, which determined the relevance of this study. The purpose of the study is to establish regulatory, economic principles for assessing the exchange of information between enterprises operating in the relevant market, in the context of compliance with legislation on protection of economic competition; analysis of the progressive international practice of cessation of violations in the form of information exchange, which leads to distortion of economic competition. In Ukraine, it is necessary to adopt the Guidelines for the Exchange of Information between Competitors (from now on referred to as "the Guidelines"), raising awareness of the business community (including associations and chambers of commerce), lawyers, and society in general regarding the main aspects of the competition compliance with competition law in order to promote fair business activities, protect the competitive environment and, as a consequence, improve consumer welfare.